The relationship between fitness variables and performance factor in keirin - Sung, B.-J.; Lee, K.-K. (Korean Journal of Sport Science, 2020)
Purpose: The purpose of this study was to examine the relationship between the track records and physical abilities in elite cyclists(keirin).